GW24-e1007 Recipe of removing both phlegm and blood stasis inhibits atherosclerosis progression and promotes plaque stability in a rabbit mode. (1st October 2013) - Ruizhen, Ji; Chenghong, Yu; Zhiqing, He; Feng, Wu; Chun, Liang; Zonggui, Wu
Abstract : Objectives: To explore the role of recipe of removing both phlegm and blood stasis in plaque progression and stabilisation in atherosclerotic rabbits. Methods: After carotid artery adventitial injury, 30 male New Zealand White rabbits were fed with an atherogenic diet for 28 weeks. From week 8 to week 28, animals were randomly divided into three groups, respectively feeding with Danlou tablets (Removing Both Phlegm and Blood Stasis group), atorvastatin tablets (statin group), and vehicle as model controls. Every 4 weeks after intervention, testing blood lipid and plasma lipoprotein oxidation level, unit LDL-C content and its degree of oxidation back to normal, then all the rabbit were killed and their carotid artery, thoracic aorta, liver, ileum were taken out to undergo pathological examination. High pressure liquid chromatography combined with fluorescence detection, immunohistochemistry and real-time RT-PCR were performed to determine MDA content, expressions og high density lipoprotein receptor (SR-BI) and lectin sample oxidised low density lipoprotein receptor (LOX-1) in plaques and experssions of liver HMG CoA reductase, 7a-hydroxylase, acetyl-CoA carboxylase, cholesterol transport protein, glucose-6- phosphatase and ileal bile acid transporter. Results: Compared with model control group, plasma LDL-C and its degree of oxidation had a significantly reduced in Removing Both Phlegm and Blood Stasis group (P < 0.05). That MDA content decreased, expressions of SR-BI receptor rised and expressions of LOX-1 receptor reduced in plaques were correlated with a reduction in the progression of plaque size and modulations in morphological features and plaque composition toward increased stabilisation, ie, more intra-plaque smooth muscle cells and collagen content, and less macrophages and lipid content. Meanwhile, compared to model control group, the liver lipid infiltration reduced, expression of HMG-CoA reductase no decreased, expression of 7a-hydroxylase, glucose-6-phosphatase rised, expression of acetyl-CoA carboxylase, cholesterol transport protein and ileum ASBT reduced that was occurred in Removing Both Phlegm and Blood Stasis group (P < 0.05). In contrast, atorvastatin treatment induced a reverse effect on liver lipid content, and expression of 7a- hydroxylase was reduced, expression of acetyl CoA carboxylase was rised, that affect liver lipid metabolism. Conclusions: Recipe of removing both phlegm and blood stasis may inhibit progression of advanced atherosclerotic plaques and promotes plaque stability, probably by improving liver cholesterol metabolism, inhibiting plasma lipoprotein oxidation and adjusting expression of plaques associated apolipoprotein receptor.